Exploring a three-factor dependence structure of conditional volatilities: Some quantile regression evidence from real estate investment trusts - Kim Hiang Liow (Journal of Risk and Financial Management, 2022)
We propose a simple three-factor pricing model, consisting of a local stock market index, a global REIT market index, and a global stock market index, to examine the dependence structure of conditional volatilities in the real estate investment trust (REIT) market from 11 countries over the sample period from 1 June 2008 to 30 April 2021. The main quantile regression results reveal that a simultaneous dependence structure exists between each REIT market and local stock, global REIT market, and global stock market. There is a positive and significant dependence between REITs and three factors for every part of the quantiles. Across each quantile, Asia-Pacific REIT markets have a consistently higher average degree of dependence with their local stock markets than with the global stock and global REIT markets, whereas European REIT markets are generally more globally integrated. Furthermore, the lower and upper quantile estimates for over half of the REIT-quantiles for the three market factors are statistically different. Additionally, some REIT markets display asymmetric co-movement with at least one of the three factors as the degree of dependence increases when these markets are booming, but the dependence level declines when the markets are bearish. This evidence of dependence across the three influential factors and REIT markets provides meaningful insights into REIT market growth, international asset pricing, risk management, and dynamic linkages in the global economy.
Keywords: 650; dependence structure; global REITs; global stocks; local stocks; quantile regression; real estate investment trusts